The role of toll-like receptors in orchestrating osteogenic differentiation of mesenchymal stromal cells and osteoimmunology - Liu, Xiaoyang; Zhou, Zongke; Zeng, Wei-Nan; Zeng, Qin; Zhang, Xingdong (Frontiers in Cell and Developmental Biology, 2023)
Osteoimmunology is a concept involving molecular and cellular crosstalk between the skeletal and immune systems. Toll-like receptors (TLRs) are widely expressed both on mesenchymal stromal cells (MSCs), the hematopoietic cells, and immune cells in the osteogenic microenvironment for bone development or repair.TLRs can sense both exogenous pathogen-associated molecular patterns (PAMPs) derived from microorganisms, and damage-associated molecular patterns (DAMPs) derived from normal cells subjected to injury, inflammation, or cell apoptosis under physiological or pathological conditions. Emerging studies reported that TLR signaling plays an important role in bone remodeling by directly impacting MSC osteogenic differentiation or osteoimmunology. However, how to regulate TLR signaling is critical and remains to be elucidated to promote the osteogenic differentiation of MSCs and new bone formation for bone tissue repair. This review outlines distinct TLR variants on MSCs from various tissues, detailing the impact of TLR pathway activation or inhibition on MSC osteogenic differentiation. It also elucidates TLR pathways' interplay with osteoclasts, immune cells, and extracellular vesicles (EVs) derived from MSCs. Furthermore, we explore biomaterial-based activation to guide MSCs' osteogenic differentiation. Therefore, understanding TLRs' role in this context has significant implications for advancing bone regeneration and repair strategies.